MODULE-BASED ACCRUAL SYSTEM OF UNIVERSITY STAFF IN-SERVICE TRAINING - Nataliya V. Chicherina; Anastasiya A. Zaitsevskaya (Высшее образование в России, 2016)
Development of the in-service training system is one of the strategic elements of the university personnel politics. In Northern (Arctic) Federal University named after M.V. Lomonosov the system of in-service training is viewed in the context of life-long academic development of the teaching staff. The article presents the University's experience of developing and implementation of module-based accrual system of in-service training which is organized in a number of priority fields of academic development: pedagogy and psychology of professional education, information-communication technologies in education, educational management and technologies of project-based work, technologies of research and innovations, internationalization in education and research.